Prevalence of dental caries in hospitalized patients with schizophrenia - Đorđević Vladan; Jovanović Mila; Miličić Biljana; Stefanović Vesna; Đukić-Dejanović Slavica (Vojnosanitetski Pregled, 2016)
Background/Aim. It is considered that over 450 million people worldwide suffer from some form of mental disorder. Previous studies in other countries have shown that schizophrenia is among the most frequent. Oral health is significant for general health and should not be separated from mental health. Studies in other countries have shown an increased incidence of carious and extracted teeth, and less incidence of filled teeth in this group of psychiatric patients. The aim of this study was to establish condition of the existing teeth, to determine the prevalence of caries and to consider possible risk factors that contribute to the current oral health status of hospitalized patients with schizophrenia. Methods. The study comprised 190 patients with schizophrenia, hospitalized at the Clinic for Psychiatric Disorders “Dr. Laza Lazarević” in Belgrade, and 190 mentally healthy patients at the Clinic for Periodontology and Oral Medicine, Faculty of Dental Medicine in Belgrade. The decayed, missing, filled (DMF) index, sociodemographic and economic characteristics were registered in both groups, as well as characteristics of the primary disease of hospitalized patients with schizophrenia. Results. The value of DMF index (representing the sum of carious, extracted and filled teeth), in the hospitalized patients with schizophrenia was 18.57 ± 7.07 and 12.47 ± 5.64 in the healthy group (p = 0.000). The structure of the DMF index in the study group showed that caries and extracted teeth dominated with 88.1%; in the control group, filled teeth dominated with 55.6%, which was a statistically significant difference for all the three observed variables. Conclusion. Hospitalized patients with schizophrenia had twice as many caries and extracted teeth, and five time less filled teeth than healthy people. The patient’s age and taking antiparkinsonics were established as predictors of the increased DMF index in hospitalized patients with schizophrenia.